KEPASTIAN HUKUM BAGI DEBITOR TERKAIT UPAYA HUKUM KASASI ATAS PUTUSAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG PASCA PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA - Andhika Putera Perdana; Yuhelson Yuhelson; Nur Hakim (SINERGI : Jurnal Riset Ilmiah, 2026)
The Constitutional Court of the Republic of Indonesia, through Decision Number 23/PUU-XIX/2021, opened the possibility for debtors to file a cassation appeal against Postponement of Debt Payment Obligation (PKPU) decisions submitted by creditors when the debtor’s proposed settlement plan has been rejected. This ruling serves as a constitutional correction to Article 235(1) and Article 293(1) of Law No. 37 of 2004, which previously denied debtors any legal remedies. However, the practical implementation within the Commercial Court remains inconsistent with the Constitutional Court’s mandate. Administrative mechanisms of the Supreme Court, including SEMA No. 1 of 2022 and Decree No. 109/2020, have yet to be aligned with this decision, resulting in debtor cassation petitions being rejected on formal grounds, as seen in several PKPU cases. This research employs a normative legal research method, utilizing statutory, case-based, historical, and analytical approaches. The study examines primary, secondary, and tertiary legal materials through qualitative juridical analysis to assess the implications of the Constitutional Court’s ruling and the form of legal certainty that should be afforded to debtors. The findings indicate that Decision 23/PUU-XIX/2021 normatively grants debtors a constitutional right to seek cassation. Nevertheless, inconsistencies in the Supreme Court’s procedural regulations have generated significant legal uncertainty for debtors. When viewed through the lens of the rule of law and legal certainty theories, such conditions contradict the principles of justice, clarity, and protection of legal subjects. Therefore, regulatory harmonization, procedural reform, and administrative adjustments at the Commercial Court level are required to ensure the effective implementation of the Constitutional Court’s decision and to guarantee genuine legal certainty for debtors